Reduced GUI for an interactive geometry software: Does it affect students' performance?. (January 2016) - Borges, Simone S.; Reis, Helena Macedo; Marques, Leonardo B.; Durelli, Vinicius H.S.; Bittencourt, Ig Ibert; Jaques, Patrícia A.; Isotani, Seiji
Abstract: Purpose: The purpose of this paper is to describe an experimental study to reduce cognitive load and enhance usability for interactive geometry software. Design/methodology/approach: The Graphical User Interface is the main mechanism of communication between user and system features. Educational software interfaces should provide useful features to assist learners without generate extra cognitive load. In this context, this research aims at analyzing a reduced and a complete interface of interactive geometry software, and verifies the educational benefits they provide. We investigated whether a reduced interface makes few cognitive demands of users in comparison to a complete interface. To this end, we designed the interfaces and carried out an experiment involving 69 undergraduate students. Findings: The experimental results indicate that an interface that hides advanced and extraneous features helps novice users to perform slightly better than novice users using a complete interface. After receiving proper training, however, a complete interface makes users more productive than a reduced interface. Originality/value: In educational software, successful user interface designs minimize the cognitive load on users; thereby users can direct their efforts to maximizing their understanding of the educational concepts being presented. Highlights: We investigated whether a reduced interface of an interactive geometry software helps to increase students' performance. We designed 60 tasks to be completed with two different interfaces, a complete and a reduced version, for the same software. We carried out an experiment involving 69 undergraduate students, randomly assigned to one of the interfaces. The experimental results indicate that the reduced interface helps novice users to perform slightly better. After receiving proper training, however, a complete interface makes users more productive using a complete interface.